Antimicrobial photodynamic therapy effectiveness against susceptible and methicillin-resistant Staphylococcus aureus biofilms - Teixeira, Camilo Geraldo de Souza [UNESP]; Sanitá, Paula Volpato [UNESP]; Ribeiro, Ana Paula Dias; Dias, Luana Mendonça [UNESP]; Jorge, Janaina Habib [UNESP]; Pavarina, Ana Cláudia [UNESP] (Elsevier, 2020)
Background: Staphylococcus aureus have a great ability to become rapidly resistant to conventional antimicrobial therapies. This study evaluated the efficacy of antimicrobial photodynamic therapy (aPDT) mediated by Curcumin (Cur) and light-emitting diode (LED) in the inactivation of biofilms of methicillin susceptible and resistant S. aureus (MSSA and MRSA, respectively). Methods: Biofilms were treated with Cur (20, 40 or 80 μM) and illuminated with LED source (455 ± 3 nm; 5.28 J/cm2) (aPDT groups), or treated either with Cur or LED only. Other samples were not exposed to Cur or LED (negative control). The biofilms viability after all experimental conditions were evaluated by counting the number of colonies (CFU/mL) and XTT assay. Additional samples were also evaluated by LIVE/DEAD® staining using confocal laser scanning microscopy (CLSM). Data were analyzed by ANOVAs followed by the Games-Howell post hoc test (α = 0.05). Results: For both strains, all aPDT groups significantly reduced both CFU/mL and metabolic activity of biofilms compared to the negative control (p < 0.001). The results were enhanced when 80 μM of Cur was used. CLSM images showed that both bacteria biofilms submitted to aPDT had a large number of red-stained colonies, especially at aPDT80. In general, MRSA biofilms tended to be less susceptible to aPDT than MSSA biofilms. Conclusions: It can be concluded that aPDT mediated by Cur and LED was an efficient method to inactivate 48 -h biofilms of both S. aureus strains.
Keywords: Antimicrobial photodynamic Therapy; Biofilm; Methicillin-resistant Staphylococcus aureus; Photochemotherapy; Staphylococcus aureus